Freedom as value of modern society (Journal of Philosophy Culture and Political Science, 2015)
In this article, freedom is seen as a social value required for comfortable development of the individual and society as a whole. Freedom is the subject of philosophical reflection long enough. The article presents a point of view according to which freedom is multifaceted manifestations - in politics, religious choice, the social sphere, science, art. The greatest importance to society is the preservation of the values of freedom of religion in politics and society. Freedom largely determines the future of the existence of other cultural experiences, and other values. The author emphasizes that freedom is a value inherent in the traditional Kazakh society, despite some theories that freedom as a value in the first place is a product of the revolutionary upheavals in Europe. In the modern Kazakh society was a certain freedom as a transformation of values. Great attention attracts the situation with freedom of conscience and freedom in the sphere of political life in Kazakhstan. In modern Kazakhstan society there is a danger of loss of freedom of choice of spiritual practices and political decision-making.
Keywords: social value; value; freedom; secular society; the transfor¬mation of society.